Inhibition of temperature-sensitive TRPV3 channel by two natural isochlorogenic acid isomers for alleviation of dermatitis and chronic pruritus - Hang Qi; Yuntao Shi; Han Wu; Canyang Niu; Xiaoying Sun; KeWei Wang (Elsevier, 2022)
Genetic gain-of-function mutations of warm temperature-sensitive transient receptor potential vanilloid 3 (TRPV3) channel cause Olmsted syndrome characterized by severe itching and keratoderma, indicating that pharmacological inhibition of TRPV3 may hold promise for therapy of chronic pruritus and skin diseases. However, currently available TRPV3 tool inhibitors are either nonselective or less potent, thus impeding the validation of TRPV3 as therapeutic target. Using whole-cell patch-clamp and single-channel recordings, we report the identification of two natural dicaffeoylquinic acid isomers isochlorogenic acid A (IAA) and isochlorogenic acid B (IAB) that selectively inhibit TRPV3 currents with IC50 values of 2.7 ± 1.3 and 0.9 ± 0.3 μmol/L, respectively, and reduce the channel open probability to 3.7 ± 1.2% and 3.2 ± 1.1% from 26.9 ± 5.5%, respectively. In vivo evaluation confirms that both IAA and IAB significantly reverse the ear swelling of dermatitis and chronic pruritus. Furthermore, the isomer IAB is able to rescue the keratinocyte death induced by TRPV3 agonist carvacrol. Molecular docking combined with site-directed mutations reveals two residues T636 and F666 critical for the binding of the two isomers. Taken together, our identification of isochlorogenic acids A and B that act as specific TRPV3 channel inhibitors and gating modifiers not only provides an essential pharmacological tool for further investigation of the channel pharmacology and pathology, but also holds developmental potential for treatment of dermatitis and chronic pruritus.